Zootopia: the depiction of multiculturalism and multicultural society through a tale of animals = Zootopia: bức tranh khắc họa chủ nghĩa đa văn hóa và xã hội đa văn hóa qua câu chuyện về loài vật - Pham, Minh Duc (2021)
This paper is an analysis of multiculturalism as depicted in Disney animated movies and examine one of the studio’s recent box office success Zootopia as a model of how far Disney has gone to bring its audience’s attention to the cultural diversity and multiculturalism phenomena. The research will begin with establish a foundation on the definition of ‘cultural diversity’ and ‘multiculturalism’, as well as the depiction of said concept on the big screen by examining previous works of both American movie industry in brief and Disney animation throughout the years. Then, Zootopia will be examined as a case study to identify the new aspects of multiculturalism that have been integrated into the movie by comparing and contrasting its characters, settings and semiotic features both with previous Disney’s movie of the same theme and with real-life historical and contemporary accounts and researchs on multicultural societies.